The Demand of Cost of Equity: Is Audit Attributes Matters? - Muhammad Dhia Ulhaq; Yossi Diantimala; Syukriy Abdullah (Riset Akuntansi dan Keuangan Indonesia, 2021)
This paper examines the impact of the audit committee on external audit attributes and the cost of equity relationship. Before that, this study investigates the impact of auditor industry specialization, auditor tenure, and audit committee on audit quality. Samples are 588 non-financial companies listed on the Indonesian Stock Exchange for the period 2015-2020. The results show that auditor industry specialization and audit committee affect audit quality positively significant. However, audit quality has no significant effect on the cost of equity. The role of the audit committee on the relationship between audit quality and cost of equity is not significant either. Auditor tenure negatively significant affects the cost of equity. Therefore, only auditor tenure matters for investors to demand the cost of equity. However, based on the audit committee's task, we realize a big role of the audit committee in audit quality and cost of equity relationship. We argue that the audit committee has the power to evaluate internal audits and external audits of a firm so the existence of an audit committee provides good signals to capital providers and lenders regarding the credibility of an effective monitoring process and therefore affects the cost of equity.Keywords: Audit quality, auditor industry specialization, audit committee, auditor tenure, cost of equity.